Forest disappearance by firewood consumption in the Amazon estuary - Tsuchiya, Akio; Hiraoka, Mario (Pontificia Universidad Católica del Perú. Fondo Editorial, 1998)
Deforestation of flooded (várzea) and non-flooded (terra firme) forests caused by firewood consumption at tile factories (olaria) was investigated in Abaetetuba Island at the Amazon estuary. Várzea is spatially limited, the area is only 3% of the whole Amazon, however, it is heavily influenced by human activities, especially by the cultivation of acaí palm (Euterpe oleracea Mart.). The trees are cut down for the olarias. The number of tree species are small, and they have less wood density than terra firme tree species because the várzea is flooded twice a day throughout the year. Terra firme forests, which are also secondary forests, receive less human impact, and have more tree species and more individual trees with a growth extension that exceeds the species in the várzea forests. The deforestation was examined by comparing forest biomass in a unit area to firewood consumption at olarias. The annual area of deforestation was estimated by using the combination of tree species in the firewood and human impact in the várzea forests. Then the estimation was extended to the whole island, assuming that the forests were rotatively cleared every 25 to 30 years. The results indicated that the area of deforestation was 6,870ha/25 years to 8,337ha/30 years, and that it was smaller than the island. However, logging is not only for fuel at olarias. If Belém's economic influence becomes stronger, and electric energy is not diffused throughout the island, the lumber consumption will accelerate and the increase might make the forest disappear faster than estimated.
Keywords: Amazon Estuary; Tile Factory (olaria); Firewood; Forest Biomass; Deforestation Area; https://purl.org/pe-repo/ocde/ford#5.07.00